Indonesia's Digital Push to Combat Literacy Crisis - Deny Firmansyah Yonanda; Ilmi Usrotin Choiriyah (Indonesian Journal of Cultural and Community Development, 2024)
This study investigates the government's role in improving literacy rates in Sidoarjo, Indonesia, where reading interest is the lowest in ASEAN. Using a descriptive qualitative method, interviews with library officials revealed that innovative programs and digital media are key to enhancing public engagement. The research highlights the Sidoarjo government's implementation of smart city applications and digital resources to support education and public services. Results indicate that practical information and effective use of digital tools are essential for increasing literacy. This study underscores the importance of government initiatives in addressing literacy challenges and improving educational outcomes. Highlights: Government Initiatives: Smart city applications and digital tools boost literacy in Sidoarjo. Low Literacy Rates: Indonesia's lowest reading interest in ASEAN needs urgent intervention. Innovative Programs: Digital media and practical information enhance public engagement and literacy. Keywords: Literacy, Government Role, Digital Media, Education, Sidoarjo